Pengaruh Disiplin Kerja, Lingkungan Kerja dan Evaluasi Kinerja terhadap Produktivitas Pegawai (Studi Kasus pada Diskominfostan di Kota Bekasi) - Muhammad Harun Al Rasyid; Anita Novialumi (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study examines the impact of work discipline, work environment, and performance evaluation on employee productivity at the Bekasi City Communication, Information, and Statistics Agency (Diskominfostandi), where productivity remains suboptimal despite digital transformation demands. Employing a quantitative approach with a saturated sampling technique, data were gathered via questionnaires from 98 civil servants (ASN) and contractual employees (TKK). Data analysis was conducted using SPSS version 27, encompassing classical assumption tests, multiple linear regression, and hypothesis testing (t-tests and F-tests). The results reveal that work discipline, work environment, and performance evaluation positively and significantly influence employee productivity, both partially and simultaneously. Notably, the work environment emerged as the most dominant factor (β = 0.462). Furthermore, the coefficient of determination (R² = 0.709) indicates that these three variables strongly explain the variance in productivity. In conclusion, enhancing work discipline, fostering a conducive work environment, and implementing effective performance evaluations are critical to significantly boosting employee productivity at Diskominfostandi.